Zarys zmian opodatkowania dochodów osobistych w Polsce - Komar, Andrzej (Wydział Prawa i Administracji UAM, 1988)
The article discusses the problem of personal income taxation reform in Poland. The proposed changes consist in introducing common income tax. The author sketches the conception of such a tax. Therefore, he discusses specific elements of the income tax construction, such as the subject of the income tax, its assessment basis, tax-rate, tax reductions and exemptions. The author declares for common taxation of income with one tax. Hence, he proposes to eliminate separate income tax for a non-socialized sector of the economy. Besides, he is also for including into income taxation the income obtained from agricultural activity (from both plant and animal production as well as from special sectors). The above postulate may evoke reservations and cause trouble in its parctical implementation. The introduction of income tax should be preceded by setting the system of personal income and prices in order. Otherwise the tax reform will be of isolated character and of limited importance. In the article the author shows the difficulties connected with the introduction of the said tax. They are of psychological and economic nature. Besides, it is also necessary to analyse in detail the existing tax law in order to eliminate inconsistency and incoherency of tax law regulations. Finally, the author points out to the need of examining American and West German examples of tax law since they contain many solutions which may be interesting from a Polish point of view.
An outline of changes in personal income taxation in Poland